A lesson in love: Farid al-Din Attar’s story of Sheikh San’an and the Christian girl - R. de Groot (Acta Theologica)
This article interprets the story of Sheikh San’an and the Christian girl from Attar’s The conference of the birds as a special case of interfaith love. The sheikh’s surprise meeting with the girl leads him to the painful insight that, although he is an accomplished and highly respected scholar, he does not know true love. Only with the help of outrageous means of humiliation, inflicted upon him by a girl of another faith, including the rejection of his own religion as he knows it, is he able to bring his path to perfection. The meeting between the sheikh and the Christian girl may be compared with the encounter between Rumi and Shamsoddin of Tabriz, in the sense that both are transformed by shock from an eminent scholar into a true lover of the divine.